Musiker als Heroen einer österreichischen Identität und Kulturpolitik in der Zwischenkriegszeit - Lenhart, Markus Helmut (Die Musikforschung, 2022)
In the aftermath of the collapse of the Austro-Hungarian Empire in 1918, the new Republic of Austria had problems to define a specific Austrian nationality. In search for such a national identity, politicians and scholars referred to a particular Austrian culture, stressing the role of music that defined Austria as a “Musikland” (land of music). A critical analysis of musicological texts published by Austrian scholars such as Robert Lach, Alfred Orel and Adolf Sandberger in the interwar years reveals a strong reliance on a narrowly circumscribed group of musicians, who were singled out as exemplary bearers of an Austrian national identity, with a strong emphasis on Viennese musical culture shaped by the native landscape. In this capacity Haydn, Mozart, Beethoven and Schubert (flanked by Brahms, Bruckner, Strauß and Wolf ) were presented to the general public as “heroes”, using not only scholarly texts but also films and music festivals for the dissemination of this musical Austrian identity.